2021
DOI: 10.3390/su13137006
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Applications of Emerging Active Travel Data: A Review of the Literature

Abstract: Active travel (AT) has the potential to integrate with, or in some cases substitute for, trips taken by motorized transportation. In this paper we review relevant research on AT outcomes to address the potential of AT and emerging data sources in supporting the transport paradigm shift toward AT. Our analysis identifies physical, mental, built and physical environmental, monetary, and societal outcomes. Traditional methods used to acquire AT data can be divided into manual methods that require substantial user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 104 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Researchers have also measured people’s health status as the sum of outcomes such as sickness and absence from work (Hansson et al, 2011; Mytton et al, 2016), long-term illness, walking difficulties and obesity (BMI) (Mattisson et al, 2018). Considering the established beneficial influence of transport physical activity on physical health (Marques et al, 2020; Alattar et al, 2021), it was no surprise that active travel modes improved objective and subjective health measures. Objectively, walking and cycling reduced sickness absence days, illness levels, walking difficulties and obesity scores (Mattisson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have also measured people’s health status as the sum of outcomes such as sickness and absence from work (Hansson et al, 2011; Mytton et al, 2016), long-term illness, walking difficulties and obesity (BMI) (Mattisson et al, 2018). Considering the established beneficial influence of transport physical activity on physical health (Marques et al, 2020; Alattar et al, 2021), it was no surprise that active travel modes improved objective and subjective health measures. Objectively, walking and cycling reduced sickness absence days, illness levels, walking difficulties and obesity scores (Mattisson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Later, the USA Physical Activity Guidelines Advisory Committee ( 2018 ) reported that transportation physical activity examples include “walking or bicycling to and from work, school, transportation hubs, or a shopping centre”. Finally, Alattar et al ( 2021 ) defined active travel as “journeys that have been undertaken either entirely or partially using human-powered transportation modes such as walking, cycling or using a wheelchair”. More recently, European researchers involved in the PASTA (Physical Activity through Sustainable Transport Approaches) project defined activities, including “walking and cycling for transport solely or in combination with public transport”, as AM (Gerike et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be realised through traditional manual counting or newer technologies such as machine learning analysis of video camera images (e.g. Foroozandeh Shahraki et al, 2017;Edwardes et al, 2021) augmented with emerging data sources (Alattar et al, 2021) such as crowdsourced data to improve the spatial and temporal granularity (Conrow et al, 2018;Kwigizile et al, 2022).…”
Section: Implications For Policy and Future Researchmentioning
confidence: 99%